Research on the Evolution Mechanism of Large Deformation of Expansive Loess Tunnel under Rainfall. (17th November 2022) - Yan, Qin; Li, Yuan; Yuan, Yang
Abstract : Large deformation, collapse, and destruction of supporting structure occurred many times due to rainfall in Xiaohegou tunnel, which is located at Taixing Railway in Shanxi Province. In this paper, the Xiaohegou tunnel is taken as an example, and the large deformation numerical simulation method is used to reproduce the collapse process of the slope at the entrance and the internal section of the tunnel. The reasons for the failure of the original initial support of the tunnel are analyzed, and the failure mechanism of the support structure of the expansive loess tunnel was clarified. The results show that the rainfall leads to the destruction of the tunnel support and the decrease of the bearing capacity of the support structure, which results in the collapse of the tunnel.